MiR-497-5p regulates ox-LDL-induced dysfunction in vascular endothelial cells by targeting VEGFA/p38/MAPK pathway in atherosclerosis - Wei Lu; Guoqing Wan; He Zhu; Tao Zhu; Xinmei Zhang (Heliyon, 2024)
Background: The impairment of endothelial cells triggered by oxidized low-density lipoprotein (ox-LDL) stands as a critical event in the advancement of atherosclerosis (AS). MiR-497-5p has been recognized as a potential predictor for AS, but its precise involvement in ox-LDL-induced endothelial cell dysfunction remains to be elucidated. Methods: An in vitro AS cell model was established by exposing human umbilical vein endothelial cells (HUVECs) to 100 μg/mL ox-LDL for 24 h. The assessment of endothelial cell function included evaluating cell viability, caspase-3 activity, inflammatory factors, and oxidative markers. Molecular mechanisms were elucidated through quantitative real-time PCR, Western blot analysis, and luciferase reporter assays. Results: Our investigation revealed that exposure to ox-LDL led to an upregulation in miR-497-5p and p-p38 levels, while downregulating the expression of vascular endothelial growth factor A (VEGFA) and phosphorylated (p)-endothelial nitric oxide synthase (p-eNOS) in HUVECs. Ox-LDL exposure resulted in decreased cell viability and angiogenic capacity, coupled with increased apoptosis, inflammation, and oxidative stress in HUVECs, partially mediated by the upregulation of miR-497-5p. We confirmed VEGFA as a direct target of miR-497-5p. Interfering with VEGFA expression significantly reversed the effects mediated by miR-497-5p silencing in HUVECs exposed to ox-LDL. Conclusions: In summary, our findings demonstrate that miR-497-5p exacerbates ox-LDL-induced dysfunction in HUVECs through the activation of the p38/MAPK pathway, mediated by the targeting of VEGFA.